Sleep patterns and the risk for unipolar depression: a review - Wiebe ST (Dove Medical Press, 2012)
Sabrina T Wiebe, Jamie Cassoff, Reut GruberAttention, Behavior and Sleep Laboratory, Douglas Mental Health University Institute, Montréal; McGill University, Montréal, Quebec, CanadaAbstract: Psychological disorders, particularly mood disorders, such as unipolar depression, are often accompanied by comorbid sleep disturbances, such as insomnia, restless sleep, and restricted sleep duration. The nature of the relationship between unipolar depression and these sleep disturbances remains unclear, as sleep disturbance may be a risk factor for development, an initial manifestation of the disorder, or a comorbid condition affected by similar mechanisms. Various studies have examined the impact of sleep deprivation on the presence of (or exacerbation of) depressive symptoms, and have examined longitudinal and concurrent associations between different sleep disturbances and unipolar depression. This review examines the evidence for sleep disturbances as a risk factor for the development and presence of depression, as well as examining common underlying mechanisms. Clinical implications pertaining to the comorbid nature of various sleep patterns and depression are considered.Keywords: sleep, depression, insomnia, sleep deprivation, development